2010
DOI: 10.1111/j.1442-200x.2010.03169.x
|View full text |Cite
|
Sign up to set email alerts
|

Cord blood thyroid‐stimulating hormone and free T4 levels in Turkish neonates: Is iodine deficiency still a continuing problem?

Abstract: Our data provide the normative data for cord blood TSH and FT(4) levels in Turkish neonates and show that iodine deficiency is a still a public health problem in Turkey. These measurements can be useful for detection and verification of hypothyroidism in a screening program for congenital hypothyroidism as well as evaluation of the success of the iodination program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…The prevalence of transient CH in Turkey is much higher than the expected rate of 5-10% reported for iodine-sufficient populations (14). Numerous studies carried out in newborns (15,16,17) and pregnant women (18,19,20) have already demonstrated that iodine deficiency is a continuing problem of Turkey. Also, a recent study revealed that iodine excess could be a problem in newborns due to use of iodine-containing antiseptics during delivery despite maternal iodine deficiency (20).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of transient CH in Turkey is much higher than the expected rate of 5-10% reported for iodine-sufficient populations (14). Numerous studies carried out in newborns (15,16,17) and pregnant women (18,19,20) have already demonstrated that iodine deficiency is a continuing problem of Turkey. Also, a recent study revealed that iodine excess could be a problem in newborns due to use of iodine-containing antiseptics during delivery despite maternal iodine deficiency (20).…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies on neonatal TSH levels and congenital hypothyroidism (CH) have yielded conflicting results . For example, in a study investigating the role of iodine deficiency in the aetiology of CH, we found that the frequency of iodine deficiency was 36% in CH patients and 88% in their mothers .…”
Section: Introductionmentioning
confidence: 99%
“…The median values of UIC in patients and their mothers were 110 and 40 μg/l, respectively. Another recent study on cord blood TSH has found a high frequency (28%) of elevated TSH concentrations . Although the results of national CH screening, implemented by the Ministry of Health since 2007, have not yet been published, the data from several studies on regional CH screening indicate that iodine deficiency may still be a public health problem in some regions in Turkey …”
Section: Introductionmentioning
confidence: 99%
“…In Turkey, there are several previous regional studies based on CH screening and neonatal TSH levels (23,24,25,26,27). In a study on incidence of CH in the West Black Sea area (Bolu, Düzce, and Zonguldak provinces), elevated blood TSH (>5 mIU/L) concentrations were 26.7% and recall rate was 1.6% between 2000 and 2002 (24).…”
Section: Discussionmentioning
confidence: 99%
“…In another study from Bursa province, between 1995 and 2004, Sağlam et al (25) reported a 5.8% recall rate and a 1/840 CH incidence, which could be explained by existence of ID. Another study on cord blood TSH of newborns showed a high frequency of elevated TSH concentrations (frequency of >10 mIU/L 28%) (26). In another recent study investigating the role of ID in the etiology of CH, ID frequency was 36% in CH patients and 88% in their mothers (27).…”
Section: Discussionmentioning
confidence: 99%